EDUCATION IN THE FORMAL AND INFORMAL PROCESSES IN ONDO STATE, NIGERIA, 2000-2008: A COMPARATIVE ANALYSIS - M.S. Jayeola-Omoyeni (European Scientific Journal, ESJ, 2013)
In the 1970’s, Ivan Illich, Dore and others were already seriously criticizing the dominance of school education in the United States of America, by pointing to the consequent devaluing of other forms of learning. Formal learning was defined purely in terms of school attendance, and, its value, in terms of grades and certificates. The formal process of learning according to Torrado (1991) follows the banking principles according to which a learner took a new knowledge in exactly the same way that money is paid into an account. This article presents a report of a project embarked upon by a group of cocoa farmers at Owena, on small communities in Ondo State, Nigeria and being a sub-station in Ibadan, Cocoa Research Institute of Nigeria (CRIN), Ibadan on the outcome of educating participants in the formal and informal processes. The report shows that a higher percentage of the participants learned freely among themselves by raising and answering questions that were beneficial to their occupations, cocoa production, (major occupation), welfare, healthy living, among others. The significance of the project is to show that adults learn less under the formal education process, learn and become more active under the informal process. The informal learning process is further recommended so as to provide a framework for meaningful learning experiences, sustain learners, make learning stimulating and lifelong among the participants.